Comparative evaluation of anesthetic efficacy and hemodynamic effects of intrathecal isobaric bupivacaine versus intrathecal isobaric levobupivacaine in the lower abdominal and lower limb surgeries - Chinthavali Sujatha,; Chandraleela Sundararajan,; Arthi Asokan, (Asian Journal of Medical Sciences, 2022)
Background: The most frequently utilized approach in patients undergoing lower abdominal and lower limb procedures is spinal anesthesia with bupivacaine. Aims and Objectives: The aim of the study was to compare the anesthetic efficacy and hemodynamic effects of isobaric bupivacaine and isobaric levobupivacaine for spinal anesthesia. Materials and Methods: In our study, 80 patients (43 – male and 37 – female) between the ages of 18 and 70 years at Sri Venkateswaraa Medical College Hospital and Research Centre, Ariyur, Puducherry, were enrolled and split into Group I and Group II following approval by an ethical committee and written informed consent. Individuals in Group I were given 3 mL of preservative free 0.5% isobaric bupivacaine (Anawin™, bupivacaine hydrochloride, Neon laboratories, India), and Group II patients were given 3 mL of 0.5% isobaric levobupivacaine (Levoanawin™, levobupivacaine hydrochloride, Neon laboratories, India) for spinal anesthesia. A complete preanesthetic checkup was performed the day before surgery. Results: In this study, we observed no significant correlation between height, weight, and surgery duration. We discovered a statistically substantial distinction in motor and sensory blockade between the bupivacaine (Group I) and levobupivacaine (Group II) groups. In this study, Group I (50% of patients) had a lower occurrence of hypotension than Group II (20% of patients), indicating a statistically significant variation between the groups. Conclusion: When compared to levobupivacaine, individuals in the bupivacaine group required more administration of the vasoactive medicine ephedrine and the sympathomimetic drug atropine. Levobupivacaine is less cardiotoxic, neurotoxic, and equally potent local anesthetic compared to its racemate.